1999
DOI: 10.1002/(sici)1096-8652(199910)62:2<65::aid-ajh1>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucocorticoids and mineralocorticoids on proliferation and maturation of human peripheral blood stem cells

Abstract: It has been shown that hematopoietic progenitors can be expanded ex vivo in the presence of various cytokine combinations. Glucocorticoids (GC) are involved in the self-renewal of erythroid progenitors in chicken. To see whether GC have a similar effect on hematopoiesis in humans, CD34(+) peripheral blood stem cells were cultured in serum free medium in the presence of a GC, triamcinolone acetonide. However, our results demonstrate an inhibition of both erythroid and granulocyte-macrophage (GM) proliferation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Our finding that CD34+ cells express the mineralocorticoid receptor is consistent with accumulating evidence that circulating progenitor cells express mineralocorticoid receptors 28, 29 and also that their growth in vitro is impaired by addition of aldosterone to the culture medium. 14 These findings are made all the more compelling by the observed reversal of these effects in vitro with the addition of spironolactone.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that CD34+ cells express the mineralocorticoid receptor is consistent with accumulating evidence that circulating progenitor cells express mineralocorticoid receptors 28, 29 and also that their growth in vitro is impaired by addition of aldosterone to the culture medium. 14 These findings are made all the more compelling by the observed reversal of these effects in vitro with the addition of spironolactone.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, steroids are well known to influence the development, differentiation and homeostasis of a large number of cells. In particular, glucocorticoids (GC) affect the differentiation of several types of stem cells such as mesenchymal [24] and neural stem [25] cells in vitro, and also have an effect on the proliferation and maturation of human peripheral blood stem cells in vitro and in vivo [26]. The migratory capacity and relative baseline levels of CD133+ cells may be influenced by chronic steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that aldosterone increases the colony formation/proliferation of granulocyte-macrophage cells and diminishes the same parameters for erythroid cells. 14 Recent experiments have shown a downregulation of the mRNAs for proliferative proto-oncogenes by aldosterone. 15 In contrast, aldosterone may mediate angiotensin II-stimulated vascular smooth muscle cell proliferation in vitro.…”
Section: Discussionmentioning
confidence: 99%